The effect of changes in co2, plasma protein, and hemoglobin on increasing blood acidity of patients with respiratory acidosis in the ICU room, dr. Slamet Martdirjo Pamekasan - Taufiqurrahman Rahman; Edy Suryadi Amin; Abdan Syakura (Jurnal Keperawatan, 2022)
Backgrounds: Character education is currently one of the solutions to overcome moral decline. From a psychological point of view, the character describes several potentials. Objectives: This study aims to determine the effect of P2KK on the soft skills of students at the University of Muhammadiyah Malang. Methods: The research design used was a pre-experimental group pre-posttest design. Sampling in this study used non-probability sampling with a quota sampling technique. The samples used were 100 students of the University of Muhammadiyah Malang class of 2018 who took part in P2KK batches 24 and 25. Data collection used the LEQ (Life Effectiveness Questionnaire) questionnaire with data analysis using the Wilcoxon test. Results: Soft skills of University of Muhammadiyah Malang students before participating in P2KK 72% had a medium category with an average value of 140, and soft skills after P2KK 76% had a medium category with an average value of 15. Based on the results of data analysis using the Wilcoxon test, significant results were obtained (p =0.00), meaning there are differences in soft skills before and after P2KK. Conclusion: There is an effect of P2KK on the soft skills of students at the University of Muhammadiyah Malang with an experiential learning approach that can improve soft skills. The most significant influence is on the attribute of controlling emotions. The UPT recommends it. P2KK to find out and evaluate the soft skill character of P2KK participants so that the training can specifically improve the soft skills that are lacking.